Osteoimmunology: The Regulatory Roles of T Lymphocytes in Osteoporosis - Zhang, Wenjuan; Dang, Kai; Huai, Ying; Qian, Airong (Frontiers in Endocrinology, 2020)
Immune imbalance caused bone loss. Osteoimmunology is emerging as a new interdisciplinary field to explore the shared molecules and interactions between the skeletal and immune systems. In particular, T lymphocytes (T cells) play pivotal roles in the regulation of bone health. However, the roles and mechanisms of T cells in the treatment of osteoporosis are not fully understood. The present review aims to summarize the essential regulatory roles of T cells in the pathophysiology of various cases of osteoporosis and the development of T cell therapy for osteoporosis from osteoimmunology perspective. As T cell-mediated immunomodulation inhibition reduced bone loss, there is an increasing interest in T cell therapy in an attempt to treat osteoporosis. In summary, the T cell therapy may be further pursued as an immunomodulatory strategy for the treatment of osteoporosis, which can provide a novel perspective for drug development in the future.